POROSITAS POROUS MATERIAL BERBAHAN BAKU SERAT TEBU DENGAN PENGIKAT PVA - Riwaldi; Agus Rino; Megasyani Anaperta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT Utilization of sugarcane bagasse waste with PVA binder as raw material for the manufacture of porous materials that function as soundproofing. Porous materials are materials with cavities or pores within their structure. The pores in porous materials can be filled with gas, air, liquid, or fluid, depending on the type of material used. Porous materials can be used as sound-absorbing materials. The research used an experimental method. In this study, the binder mass used was the same while the bagasse mass was varied to obtain a ratio of binder to bagasse of 17:6, 17:15, 17:24. The design of the porous material obtained an average pore diameter of 256.6 μm, the average distance between pores obtained was 780.85 μm and the fiber diameter obtained was 357 μm. Kinematically, the pores formed in the porous material are closed pores. The percentage of porosity in the porous material is 76% and the resistivity value is 326.271 Pa.s/m2. The physical properties of the porous material made from sugarcane fiber with a PVA binder, in sample 1 with a thickness of 1.4 cm has a water content of 28% and a density value of 0.3002 gr/cm3. In sample 2 with a thickness of 1.7 cm, the water content is 25% and the density value is 0.3596 gr/cm^3. In sample 3 with a thickness of 2.0 cm, the water content is 24% and the density value is 0.3949 gr/cm^3. Based on the research results, the porosity of the porous material made from sugarcane fiber with a PVA binder produces a material with an average pore diameter of 256.6 μm or 256600 nm. Based on its size, this porosity is included in the macropore section, namely the type of pores with a size larger than 50 nm, more suitable for absorbing low-frequency sound.